Virtual UIST 2020: Overview of A Design Journey - Iqbal, Shamsi; MacLean, Karon (2021)
ACM UIST 2020 took place virtually in 2020, with the main program on Oct 21-23. Originally scheduled to take place in Minneapolis, USA, collocated with our sister conference ACM CSCW, the switch to virtual meant that we needed a complete overhaul of how we planned and ran the conference. We would like to share the decisions we made and the underlying considerations behind our decision making with the hope that this may be useful to other conference planners as they plan for virtual or hybrid conferences in the near and long-term future. Since this was the first time UIST was virtual, we also created extensive documentation detailing key components - e.g technical infrastructure, how-to-guides for participants and so on. The list of additional documentation is available at the end of this document.